2018
DOI: 10.1038/s41598-018-24978-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between digestive efficiency and metabolomic profiles of serum and intestinal contents in chickens

Abstract: The increasing cost of conventional feedstuffs has bolstered interest in genetic selection for digestive efficiency (DE), a component of feed efficiency, assessed by apparent metabolisable energy corrected to zero nitrogen retention (AMEn). However, its measurement is time-consuming and constraining, and its relationship with metabolic efficiency poorly understood. To simplify selection for this trait, we searched for indirect metabolic biomarkers through an analysis of the serum metabolome using nuclear magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
1
17
0
1
Order By: Relevance
“…The LC-HRMS approach applied to lipidic fractions led to a PLS-DA model with similar explicative abilities R 2 Y (0.82 vs 0.77) and higher predictive abilities Q 2 (0.80 vs 0.48) than the previous PLS model fitted to metabolites from serum polar extracts identified by NMR to predict the quantitative value of AMEn (Beauclercq et al, 2018). This could be explained by a higher sensitivity of LC-HRMS (nM to pM) in comparison to NMR (μM to mM) (Goldansaz et al, 2017) or a lipophilic fraction more related to DE variations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LC-HRMS approach applied to lipidic fractions led to a PLS-DA model with similar explicative abilities R 2 Y (0.82 vs 0.77) and higher predictive abilities Q 2 (0.80 vs 0.48) than the previous PLS model fitted to metabolites from serum polar extracts identified by NMR to predict the quantitative value of AMEn (Beauclercq et al, 2018). This could be explained by a higher sensitivity of LC-HRMS (nM to pM) in comparison to NMR (μM to mM) (Goldansaz et al, 2017) or a lipophilic fraction more related to DE variations.…”
Section: Resultsmentioning
confidence: 99%
“…In a prior study, we showed that the metabolomics profile of the hydrosoluble fraction of serum was linked to DE (Beauclercq et al, 2018). In this study, we observed that the color of serum seemed to differ between efficient and non-efficient birds, thus suggesting that pigments also differed between the two lines.…”
Section: Introductionmentioning
confidence: 99%
“…Both the metabolites are involved in pyrimidine metabolism and are part of the cecal content of digestive segments involved with direct or indirect synthesis or utilization of compounds by the gut microbiota 36 . These metabolites were also reported to be affecting the digestive efficiency in chickens 37 . Previous studies have shown an increase in the concentration of xanthine by increased FI 38,39 .…”
Section: Discussionmentioning
confidence: 96%
“…Wang et al indicated that plasma alanine and proline were potential biomarkers for feed efficiency in Duroc and Landrace pigs due to their important roles in the metabolism of alanine, arginine, and proline [51]. Other studies have demonstrated that serum concentrations of glycine, histidine, lysine, and serine were associated with diverging RFI of different broiler chicken lines which may be attributed to their contributions to protein biosynthesis and ammonia recycling [52,53]. Additionally, certain organic acids, such as 4-aminobutyric acid, 3phenylpropanoic acid, and phenylacetic acid are involved in many biological processes: modulating glucose and lipid metabolism, regulating energy homeostasis, and exerting antioxidant, anti-inflammatory, and neuroprotective actions [54][55][56].…”
Section: Discussionmentioning
confidence: 99%